Designing VR Music Game for Stress Reduction - Kim, Kirak; Kim, Hyojin; Choi, Youjin; Nam, Juhan; Lee, Jeongmi (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2025)
Many individuals experience everyday stress. Effective stress management in daily life is crucial before this stress accumulates. Music has been extensively studied as a method for reducing stress. In particular, music therapy is widely used to reduce stress and enhance the well-being of various clinical groups. However, traditional music therapy has physical constraints that require patients to visit a therapeutic location. VR music therapy has been studied to address these issues, but most research focuses on receptive music therapy, failing to utilize VR's interactive potential fully. Additionally, the potential of applying gamification to VR active music therapy to enhance user engagement and encourage long-term use of the therapy application has not been explored. This paper proposes VR active music therapy based on conventional rhythm-following music therapy methods and VR gamified active music therapy by adding game elements based on Self-Determination Theory (SDT). Our between-subject comparative study (n=33) revealed the stress reduction effects of VR receptive music therapy, VR active music therapy, and VR gamified active music therapy. Importantly, participant interviews provided valuable insights into the user experiences with each VR content, confirming the potential for long-term use of VR gamified active music therapy. Moreover, this research delves into the effect of gamification on stress reduction. Through pilot test and experiments, we identify game elements that could potentially increase stress and provide guidelines for applying gamification to mitigate these factors, thereby enhancing the effectiveness of VR gamified active music therapy.